2021
DOI: 10.1186/s40478-021-01248-w
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse leptomeningeal glioneuronal tumour (DLGNT) in children: the emerging role of genomic analysis

Abstract: Diffuse leptomeningeal glioneuronal tumours (DLGNT) represent rare enigmatic CNS tumours of childhood. Most patients with this disease share common radiological and histopathological features but the clinical course of this disease is variable. A radiological hallmark of this disease is widespread leptomeningeal enhancement that may involve the entire neuroaxis with predilection for the posterior fossa and spine. The classic pathologic features include low- to moderate-density cellular lesions with OLIG2 expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 58 publications
0
22
1
Order By: Relevance
“…5 CSF analysis typically reveals a mild hyperproteinaemia and lymphocyte pleocytosis, and is done to exclude an infectious aetiology; tumour cells are rarely identified. 3,6 To date only two other case reports of DLGNT have described neoplastic cells in the CSF. 5,7 In both, however, the supportive cytology findings emerged later in the disease, subsequent to histopathological diagnosis, and were therefore not critical in guiding work-up.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 CSF analysis typically reveals a mild hyperproteinaemia and lymphocyte pleocytosis, and is done to exclude an infectious aetiology; tumour cells are rarely identified. 3,6 To date only two other case reports of DLGNT have described neoplastic cells in the CSF. 5,7 In both, however, the supportive cytology findings emerged later in the disease, subsequent to histopathological diagnosis, and were therefore not critical in guiding work-up.…”
Section: Discussionmentioning
confidence: 99%
“…This is challenging; tumour material from biopsies is typically sparse and initial biopsies are frequently non‐diagnostic 2 . Cytological diagnosis via cerebrospinal fluid (CSF) is pragmatically more feasible; however, existing cases have largely failed to identify neoplastic cytology 2–4 . We report a case of DLGNT in which CSF analysis determined the diagnosis and guided subsequent work‐up.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Additionally, DLGNTs have been associated with KIAA1549-BRAF gene fusion and 1p deletion or 1p/19q co-deletion (2,3). Given the rarity of this tumor type, its histological, radiological, and clinical features and pattern of progression remain to be fully elucidated (4).…”
Section: Introductionmentioning
confidence: 99%
“…Although they frequently occur as leptomeningeal tumors (5), some studies have reported DLGNTs without leptomeningeal dissemination, which manifests as intraspinal or intracerebral cystic or solid masses (6)(7)(8). Notably, clinical follow-up is often incomplete, and some patients present with indolent chronic disease while others experience an aggressive clinical course (4). Moreover, the differential diagnosis often includes tuberculous meningitis, cryptococcal neoformans meningitis, and meningeal metastatic tumor.…”
Section: Introductionmentioning
confidence: 99%